Snapdragons: my dog needs a bone - Hawes, Alison; Hendra, Sue (Oxford University Press Oxford, 2004)
When a girl has a new dog, she goes with her father to the market with a list of things to buy. She has definite ideas about what she wants, but the dog chooses it's own bed